Selection, optimization, and compensation: The structure, reliability, and validity of force-choice versus Likert-type measures in a sample of late adolescents. - Johnson, Sara K. ; Geldhof, G. J.; Gestsdottir, S.; Stefannson, K. K.; Bowers, E. P.; Lerner, Richard M. (Tufts University. Tisch Library., 2016)
Intentional self-regulation (ISR) undergoes significant development across the life span. However, our understanding of ISR’s developmentand function remains incomplete, in part because the field’s conceptualization and measurement of ISR vary greatly. A key samplecase involves how Baltes and colleagues’ Selection, Optimization, and Compensation (SOC) model of ISR, which was developedwith adult populations, may be applied to understand and measure adolescent self-regulation. The tripartite structure of SOC identifiedin older populations has not been replicated in adolescent samples. This difference may be due to measurement issues. In thisarticle, we addressed whether using a Likert-type format instead of a forced-choice format of the SOC Questionnaire resulted in atripartite factor structure when used with an adolescent population. Using data from 578 late adolescents who participated in the 4-HStudy of Positive Youth Development (70.80% female), we showed that the two versions of the measure produced a similar factorstructure and were similar in terms of reliability and validity, although the traditional forced-choice version provided data with slightlylower criterion validity. We therefore conclude that both types of the measure are acceptable, but the choice of measure may dependon the sample in question and the analytical approach planned for the findings. We discuss the implications of our findings for futureresearch